THE VALUE OF VISCOSITY COEFFICIENT OF COOKING OIL RESULTED BY PURIFICATION BASED ON ACTIVE CHARCOAL TEMPERATURE WITH THE FALLING BALL METHOD - Rachmawati, Dewi Oktofa; Suswandi, Iwan; Risha, Nurfa (Indonesian Physical Review, 2022)
A change in viscosity indicates the damage to cooking oil. The value of the viscosity coefficient indicates the level of viscosity. This value describes the drag caused by friction between the cooking oil molecules to block the flow. The adhesive property of used cooking oil with a high viscosity value is that it is easy to stick to foodstuffs processed with this oil. Used cooking oil is cooking oil with a high viscosity coefficient value. This oil contains free fatty acids that are harmful to the body. Reuse of used cooking oil for frying foodstuffs is not recommended. Purifying used cooking oil is one way to make cooking oil safe to consume again. The surface adsorption capacity of activated charcoal is increased by heating. Activated charcoal activation temperatures are 27oC, 40oC, 50oC, 70oC, and 90oC.The value of the viscosity coefficient of the purified cooking oil is interesting to study for the activation temperature of the activated charcoal used. The falling ball method was chosen to determine the value of the viscosity coefficient. This method measured the time the ball fell in the oil. Data were analyzed quantitatively descriptively and presented in graphical form. The results show that the value of the viscosity coefficient of the purified cooking oil decreases with the increase in the activated charcoal temperature. The value of the viscosity coefficient of cooking oil as a result of purification using activated charcoal at 90oC is (0.854 ±0.004) Pa. s